Strengthening Maternal Social Support and Promoting Child Dental and Oral Health Through SIKATIN (Tooth Brushing Reminder App) - Sosiawan, Agung; Mahiswari, Diyang; Wardi, Ully Nafisah; Hadinata, Daniel; Anjani, Nindya Rizki; Roselle, Veronica Regina; Nugroho, Sepdhyo Wahyu; Ramadhani, Maya Eka; Rumokoi, Rauhansen Bosafino; Sholihah, Naimatus; Afidati, Yasinta Izzah (Indonesian Journal of Dental Medicine, 2020)
Background: Downloadable health applications are nothing new for the public. Smartphone use has been steadily increased in years, including increased smartphone use in mothers of kindergarten students in Made Urban Village, Surabaya. Therefore, smartphone applications can be effective media in promoting child dental and oral health. The prevalence of caries in Made Kindergarten was 95%, and it was concerning. Therefore, the SIKATIN app works byreminding mothers about tooth brushing schedules for their children and motivating them to pay extra care for children's dental and oral health. Purpose: Mothers are motivated to maintain their children's dental and oral health. Method: The empowerment program helped to promote the SIKATIN app use, and the evaluation was based on the total download.Results: 100% of mothers of kindergartners achieved all indicators of success. Conclusion: 100% of the mothers of kindergartners in Made Urban Village has downloaded the SIKATIN application.